2006
DOI: 10.1080/02786820500380271
|View full text |Cite
|
Sign up to set email alerts
|

Major Source Categories for PM2.5in Pittsburgh using PMF and UNMIX

Abstract: An objective of the Pittsburgh Air Quality Study was to determine the major sources of PM 2.5 in the Pittsburgh region. Daily 24-hour averaged filter-based data were collected for 13 months, starting in July 2001, including sulfate and nitrate data from IC analysis, trace element data from ICP-MS analysis, and organic and elemental carbon from the thermal optical transmittance (TOT) method and the NIOSH thermal evolution protocol. These data were used in two source-receptor models, Unmix and PMF. Unmix, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
74
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 52 publications
3
74
1
Order By: Relevance
“…Pekney et al 65 enhanced their analysis by including organic markers in the PMF model. A few organic classes have been shown to be effective source indicators, including hopanes for vehicle exhaust, levoglucosan for vegetative burning, and n-alkanes for vegetative detritus (Table 2).…”
Section: How Well Can We Identify and Quantify Source Contributions Umentioning
confidence: 99%
See 4 more Smart Citations
“…Pekney et al 65 enhanced their analysis by including organic markers in the PMF model. A few organic classes have been shown to be effective source indicators, including hopanes for vehicle exhaust, levoglucosan for vegetative burning, and n-alkanes for vegetative detritus (Table 2).…”
Section: How Well Can We Identify and Quantify Source Contributions Umentioning
confidence: 99%
“…A few organic classes have been shown to be effective source indicators, including hopanes for vehicle exhaust, levoglucosan for vegetative burning, and n-alkanes for vegetative detritus (Table 2). Because organic markers were not measured in all samples at Pittsburgh (e.g., 24% of the sampling days), gaps were filled with the geometric mean concentration and assigned an uncertainty of four times the average precision, as suggested by Polissar et al 92,93 Although the effect of this approximation has not been systematically evaluated, Pekney et al 65 found that all of the hopanes were correlated with a primary OC/EC factor, and this was assigned to mobile source emissions. The final PMF solution contained 11 factors, with the primary OC/EC factor split into two factors: one associated with vehicle exhaust and road dust, and the other associated with vegetative burning, cooking, and vegetative detritus.…”
Section: How Well Can We Identify and Quantify Source Contributions Umentioning
confidence: 99%
See 3 more Smart Citations